Mandibular changes after rapid maxillary expansion. Literature review - Aliaga-Meza, Anthuaneth (2021)
The objective of this literature review is to report dentoalveolar and skeletal changes of the mandibular arch after rapid maxillary expansion (RMS) in mixed dentitions. An electronic search was carried out in the following databases: Medline/PubMed, Scopus, LILACS as well as manual search in the main orthodontic journals (American Journal of Orthodontics and Dentofacial Orthopedics, The Angle Orthodontics, Seminars in Orthodontics) and Google Scholar. The eligibility criteria included all studies related to the topic being reviewed, in English and Spanish, without restrictions on the year of publication. Of a total of 62 articles found, 10 were chosen to be analyzed. Quite a few authors agree on the presence of clinically significant spontaneous skeletal and dentoalveolar changes, in the mandibular dental arch in short and long term after RMS. During the aftermath of the RMS, an anterior mandibular displacement could be observed due to the overexpansion of the maxilla, in addition, dentoalveolar changes and an increase in the width of the dental arches were recorded.